2013
DOI: 10.1371/journal.pone.0068703
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol Induces Mitotic Arrest, Apoptosis, and Synergistic Cytotoxicity with Arsenic Trioxide in Human Urothelial Carcinoma Cells

Abstract: 2-Methoxyestradiol (2-ME), an endogenous derivative of 17β-estradiol, has been reported to elicit antiproliferative responses in various tumors. In this study, we investigated the effects of 2-ME on cell viability, proliferation, cell cycle, and apoptosis in human urothelial carcinoma (UC) cell lines. We used two high-grade human bladder UC cell lines (NTUB1 and T24). After treatment with 2-ME, the cell viability and apoptosis were measured by MTT assay and flow cytometry (fluorescence-activated cell sorting),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Indeed, accumulation of ROS was accompanied by upregulation of SOD activity in MCF-7 cells (Fig. 1B) which is known from the literature [21] and from our previous results [20] as the least sensitive cell line to HYP-PDT. On the other hand, we have not observed any significant increase of SOD activity in MDA-MB-231 cells neither at 1 h nor at 3 or 12 h after HYP-PDT (Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Indeed, accumulation of ROS was accompanied by upregulation of SOD activity in MCF-7 cells (Fig. 1B) which is known from the literature [21] and from our previous results [20] as the least sensitive cell line to HYP-PDT. On the other hand, we have not observed any significant increase of SOD activity in MDA-MB-231 cells neither at 1 h nor at 3 or 12 h after HYP-PDT (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Based on previous results of our group [20] as well as the findings of Vandenbogaerde et al [21] that MCF-7 cells are the least sensitive to HYP-PDT, we decided to shed more light on this issue and take a look on SOD-2 and its role in susceptibility to PDT. In this regard our aim was to monitor the correlation between the ROS and SOD activity after HYP-PDT in MCF-7 and MDA-MB-231 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in prolidase activity in these cells was accompanied by an increase in proline levels in cytoplasm. It is well recognized that MOE induces mitotic arrest and apoptosis in carcinoma cells [31]. However, in ovarian carcinoma cells lacking PRODH/POX [32], on the contrary, MOE stimulated cell proliferation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Its activation will subsequently cleave some specific substrate, such as PARP, which is a DNA repair enzyme. Furthermore, cleavage of PARP resulted in chromosomal DNA break, finally leading to cell apoptosis [37][38][39]. Our results indicate that Se-SE prevented activation of caspase-3 and cleavage of PARP caused by hIAPP in INS-1E cells, suggesting that the protective effects of Se-SE was mediated through inhibiting the caspase-mediated pathway.…”
Section: Discussionmentioning
confidence: 65%
“…Excessive ROS may induce damage of mitochondrial enzymes, DNA mutation and lipid peroxidation of membranes. Moreover, ROS are known to affect mitochondrial membrane potential and trigger a series of mitochondria-associated events that initiate apoptosis [37,40]. Previous findings suggested that overproduction of ROS was involved in hIAPP-induced beta cell toxicity [35,41].…”
Section: Discussionmentioning
confidence: 99%